Development of HOTS Problem Oriented Circle Learning E-Module to Improve Problem Solving Ability of Class VIII Students - Srinivasa, Putu Winy; Suparta, I Nengah; Ardana, I Made (Jurnal Pendidikan MIPA, 2023)
Problem solving ability is one of the important skills for students in dealing with problems in everyday life. One effort that is indicated to improve students' problem-solving abilities is to practice questions that are in the realm of High Order Thinking Skills (HOTS). This study aims to develop HOTS problem-oriented Mathematics E-Modules. The E-Module was developed using the Notion application and circle material for class VIII SMP. This study used class VIII students of SMP Negeri 2 Kuta as research subjects. The development method using 4D model stage. Data were collected using expert validation questionnaires, teacher response questionnaires and student response questionnaires as well as tests of problem-solving skills. Data analysis was carried out by calculating the average score of expert validation and the average score of the student response questionnaire. The testing of the problem-solving ability test instrument was carried out by item analysis and the internal consistency of the test items. The validation results from 2 validators obtained an average value of 4.03, which means that the E-Module is in the valid criteria. Based on the teacher's response questionnaire, an average value of 3.39 was obtained which was in the practical criteria, while based on the student response questionnaire, the average value was 3.60 which was in the very practical criteria. Furthermore, the results of the gain score for tests of students' problem-solving abilities obtained an average of 61.72 which is in the effective category.Keywords: e-module, hots questions, problem solving ability.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp248-263